PENGEMBANGAN PENGGUNAAN UJI SCHELLONG, PEMETAAN DAN PENGELOLAAN TONUS SIMPATIS Hubungan antara Hasil Uji Schellong dengan Faktor Kepribadian,Pajanan Surat Al-Hujurat dan Status Saraf Otonom - , Zaenal Muttaqien Sofro, dr.; , Prof. dr. Sri Kadarsih, S., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Autonomic Nervous System (ANS) in human being has evolved and involved in the regulation of social behaviors. Schellong test can be used to identify the activity of ANS. The sympathetic dominance can disrupt the individual's health. It is necessary to study the correlation between ANS and personality factors. Slow pace of reciting Qur'an improve MVN activity. Objective: to develop Schellong Test as a reference for maintaining health. Method: 1. Observational study. Some 2287 (PLN employees) performed Schellong and personality test. A total number of 196 subjects were recruited to determine ANS pattern. Chi Square and Regression Testing were used for statistical analysis. 2. Experimental study. A pre-posttest control group was employed. A number of 506 Mualiminâs student were recruited, 100 students were exposed to recitation divided into experimental and control group by random. Statistical analysis used were independent t-, McNemarâs Chi-Square and regression tests. The software analysis tool used was STATA version 9. Result: observational study showed that NST and AST were 30.6 % and 60.4 % respectively. Signioficant correlation was observed between personality factors and Schellong Test : HR and both N and O (pâ¤ 0.05), BP and A, O and C (p â¤ 0,05). Experimental study showed NST of experimental and control group were 10% and 2% respectively (p â¤ 0.001). The activity of myelinated vagal nerve improved in the experimental group (p â¤ 0.05). Conclusion: The percentage of NST was much lower than AST. Schellong test was shown to be correlated with personality factors. The experimental group showed reduced NST and improved the activity of myelinated vagal nerve.